1998
DOI: 10.1128/iai.66.1.191-196.1998
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cell Injury Caused by Candida albicans Is Dependent on Iron

Abstract: Although it is known that Candida albicans causes endothelial cell injury, in vitro and in vivo, the mechanism by which this process occurs remains unknown. Iron is critical for the induction of injury in many types of host cells. Therefore, we investigated the role of iron in Candida-induced endothelial cell injury. We found that pretreatment of endothelial cells with the iron chelators phenanthroline and deferoxamine protected them from candidal injury, even though the organisms germinated and grew normally.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 38 publications
1
14
0
1
Order By: Relevance
“…Furthermore, when MAC-T cells were incubated with DFO alone, no significant increase in LDH release was observed after 24 h, showing that DFO was not intrinsically toxic. This is consistent with another in vitro study performed on human endothelial cells, which reported that DFO did not increase cell susceptibility to exogenous oxidants after 48 h (Fratti et al, 1998). Furthermore, DFO has been shown to be protective in various models of ROS-induced cellular injury as reviewed by van Asbeck (1990).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, when MAC-T cells were incubated with DFO alone, no significant increase in LDH release was observed after 24 h, showing that DFO was not intrinsically toxic. This is consistent with another in vitro study performed on human endothelial cells, which reported that DFO did not increase cell susceptibility to exogenous oxidants after 48 h (Fratti et al, 1998). Furthermore, DFO has been shown to be protective in various models of ROS-induced cellular injury as reviewed by van Asbeck (1990).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, in the oral cavity, onset of candidiasis correlates with the progression of HIV disease (Klein et al, 1984;Dodd et al, 1991;Katz et al, 1992). Indeed, the requirement of the high-affinity iron permease (CaFtr1p) for infections in a mouse model, the requirement of siderophore transporter (Arn1p) for epithelial invasion and the iron- dependent endothelial cell injury caused by C. albicans have established a role for iron in systemic infections (Fratti et al, 1998;Ramanan and Wang, 2000;Heymann et al, 2002). This introduces the possibility that iron availability may play a role in signalling or facilitating the commensal to pathogenic transition in C. albicans.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that FTR1, a high-a¤nity iron permease localised in the cell surface, contributes to virulence in the mouse systemic model, while a second, di¡erently regulated permease, FTR2, does not [100]. FET3, a gene involved in iron uptake, is not essential for virulence but the fet3v mutant showed a reduced adherence to ¢broblasts [81], although iron is necessary for adherence to epithelial cells [101] and this mutant showed reduced growth in iron-limited medium [81]; it thus seems that other factors would be needed to transform a lack of adherence into the absence of virulence in the model tested [94,102]. Recently, RBT2, a gene encoding a putative secreted protein with similarity to ferric reductases, has been cloned in a di¡erential screen for genes overexpressed in the absence of TUP1.…”
Section: Metabolic Genesmentioning
confidence: 99%